Population‐based study of long‐term functional outcomes after prostate cancer treatment. (23rd June 2015) - Carlsson, Sigrid; Drevin, Linda; Loeb, Stacy; Widmark, Anders; Lissbrant, Ingela Franck; Robinson, David; Johansson, Eva; Stattin, Pär; Fransson, Per
Abstract : Objective: To evaluate long‐term urinary, sexual and bowel functional outcomes after prostate cancer treatment at a median (interquartile range) follow‐up of 12 (11–13) years. Patients and Methods: In this nationwide, population‐based study, we identified 6 003 men diagnosed with localized prostate cancer (clinical local stage T1–2, any Gleason score, prostate‐specific antigen <20 ng/mL, NX or N0, MX or M0) between 1997 and 2002 from the National Prostate Cancer Register, Sweden. The men were aged ≤70 years at diagnosis. A control group of 1 000 men without prostate cancer were also selected, matched for age and county of residence. Functional outcomes were evaluated with a validated self‐reported questionnaire. Results: Responses were obtained from 3 937/6 003 cases (66%) and 459/1 000 (46%) controls. At 12 years after diagnosis and at a median age of 75 years, the proportion of cases with adverse symptoms was 87% for erectile dysfunction/sexual inactivity, 20% for urinary incontinence and 14% for bowel disturbances. The corresponding proportions for controls were 62, 6 and 7%, respectively. Men with prostate cancer, except those on surveillance, had an increased risk of erectile dysfunction compared with the men in the control group. Radical prostatectomy was associated with an increased risk of urinary incontinence (odds ratio [OR] 1.89, 95% confidence interval [CI] 1.36–2.62) and radiotherapy increased the risk of bowel dysfunction (OR 2.46, 95% CI 1.73–3.49) compared with men in the control group. Multi‐modal treatment, in particular treatment including androgen deprivation therapy (ADT), was associated with the highest risk of adverse effects; for instance, radical prostatectomy followed by radiotherapy and ADT was associated with an OR of 3.74 (95% CI 1.76–7.95) for erectile dysfunction and an OR of 3.22 (95% CI 1.93–5.37) for urinary incontinence. Conclusion: The proportion of men who experienced a long‐term impact on functional outcomes after prostate cancer treatment was substantial.